Reducing opioid related deaths for individuals who are at high risk of death from overdose: a co-production study with people housed within prison and hostel accommodation during Covid-19 - Campbell, Anne; Millen, Sharon; Guo, Li; Jordan, Uisce; Taylor-Beswick, Amanda; Rintoul, Chris; Diamond, Aisling (Frontiers in Public Health, 2023)
Abstract Background: In 2020, opioid-related deaths in Northern Ireland reached a record high. This co-production study set out to refine the design of a wearable device for opioid users to detect a potential overdose situation. Methods: The study encompassed a ‘co-production’ phase and a ‘wearable’ phase and purposive sampling was used to recruit people who had substance use disorders and were living in a hostel and prison. The co-production phase included three focus groups with the participant group. During the wearable phase the participant group tested out the feasibility of the wearable technology in a controlled environment. This included testing the transferability of data from the device to a backend service on the cloud. Results: In the co-production phase, all participants expressed an interest in the wearable technology when it was presented to them and agreed, that in principle, such a device would be extremely beneficial to help reduce the risk of overdose within the active drug using community. Participants outlined factors which would help or hinder the design of this proposed device and their decision to wear it, if it were readily available to them. In the wearable phase, it was feasible to use a wearable device for monitoring opioid users’ biomarkers remotely. The provision of information regarding the specific functionality of the device was considered key and could be disseminated via front line services. The data acquisition and transfer process would not be a barrier for future research. Conclusion: Understanding the benefit of novel technologies such as a wearable device to improve our responses and prevent opioid-related deaths, will be critical for improving the health of people who use and inject drugs into the future.